2022
DOI: 10.3390/microorganisms10020376
|View full text |Cite
|
Sign up to set email alerts
|

Olive Fungal Epiphytic Communities Are Affected by Their Maturation Stage

Abstract: The phyllosphere comprises the aerial parts of plants and is colonized by a great diversity of microorganisms, either growing inside (as endophytes) or on the surface (as epiphytes) of plant tissues. The factors that structure the diversity of epiphytes and the importance of these microorganisms for host plant protection have been less studied when compared to the case of endophytes. In this work, the epiphytic fungal communities from fruits of the olive tree (olives) in different maturation stages (green and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…The leaf-associated fungal abundance of Ginkgo biloba was significantly higher in May than in October, which may be related to the different maturation of leaves. Studies have shown that significant differences in epiphytic fungal richness were observed among olives obtained in different production systems and maturation stages [ 55 ]; whereas, in the same production system, there was no statistical significance in richness regarding olive cultivars, and this result is consistent with the reports of epiphytic fungal communities in olives [ 56 ] and mango fruits [ 57 ] from different cultivars studied using culture-dependent methods. The screening role of host plant species on the epiphytic fungal communities [ 38 , 43 ] has been fully confirmed and attributed to different ecological strategies as well as the chemical and functional properties of host plants.…”
Section: Discussionsupporting
confidence: 85%
“…The leaf-associated fungal abundance of Ginkgo biloba was significantly higher in May than in October, which may be related to the different maturation of leaves. Studies have shown that significant differences in epiphytic fungal richness were observed among olives obtained in different production systems and maturation stages [ 55 ]; whereas, in the same production system, there was no statistical significance in richness regarding olive cultivars, and this result is consistent with the reports of epiphytic fungal communities in olives [ 56 ] and mango fruits [ 57 ] from different cultivars studied using culture-dependent methods. The screening role of host plant species on the epiphytic fungal communities [ 38 , 43 ] has been fully confirmed and attributed to different ecological strategies as well as the chemical and functional properties of host plants.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, the epiphytic fungal communities present in olive cultivars displaying different tolerance to anthracnose have been described as well (Castro et al, 2022) (Table 3). In this study neither the cropping system nor the plant genotype significantly influenced the composition of the fungal community, while the fruit maturation stage produced a strong impact on the epiphytic mycobiome.…”
Section: Unveiling the Olive Microbiome And Factors Influencing Its C...mentioning
confidence: 99%
“…Olive (Olea europaea L.) is a main crop cultivated within the Mediterranean region due to its local and historically high socioeconomic importance. It is putatively expanding cultivation on a global scale due to the growing awareness in olive oil's consumption's health benefits, and, furthermore, as a rich source (including drupes, olive oil, and olive drupe processing byproducts) of biologically active compounds valuable for food, cosmetic, and pharmaceutical industries [25][26][27]. Though moderately tolerant to abiotic stress such as drought and salinity [28], the olive tree is host for many pests and a variety of pathogenic microorganisms, mainly fungi, resulting in a multitude of diseases and consequent decrease in tree fitness, productivity, and oil quality [29].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several metagenomics studies regarding the epiphytic and endophytic mycoflora of olive phyllosphere and carposphere are available. These span the analysis of fungal diversity under different phenological stages [53], composition of microbial epiphytical communities on olive drupe in relation to maturation process and genotype [25], phyllosphere endophytic mycobiome of different cultivars [26], and host-pathogen interactions in association with the phyllosphere mycobiome [27,54]. Similar approaches regarding spoilage microorganisms during fermentation [55], effect of salt stress on leaf endophytic bacterial communities of different cultivars [56], or the genotype effect on bacterial populations [57], provide data on the shapes of phyllosphere or carposphere bacterial communities.…”
Section: Introductionmentioning
confidence: 99%